Level of Self Objectification in Teenage School Girls: Causes, Consequences and Concerns - et. al., Mansi Dwivedi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Self-Objectification is the tendency to encounter one's body principally as an item, to be assessed for its appearance rather than for its effectiveness. The objectification theory suggests that females more so than males consider a spectator's viewpoint as their primary view on their actual selves. This self-objectification often prompts expanded sensations of shame, anxiety, and disgust toward oneself. It decreases opportunities for top inspirational states, and reduces familiarity with inner bodily states. Self-objectification is fundamentally a manifestation of sexual objectification which is highly prevalent in the society. Calogero (2005) claimed that the females view themselves through the lens of an external spectator and this habitual monitoring leads to body shame, appearance anxiety, depression and disordered eating. Adolescents and specially females are more worried about their physical appearance as opposed to their merits and capabilities. The Aim of this study was to assess the level of Self Objectification among 100 adolescent girls of Uttar Pradesh. The data was collected using Objectified Body Consciousness Scale by McKinley, N.M., & Hyde, J.S. (1996). A comparative analysis of the level of self-objectification in adolescent girls of Lucknow and Agra was also conducted. The results revealed that 77% of girls fall under the category of moderately high objectification and the adolescent girls of Lucknow city are scored more on self objectification as compared to the adolescent girls of Agra.The subscales used in the OBC scale are (a) surveillance (viewing the body as an outside observer), (b) body shame (feeling shame when the body does not conform), and (c) appearance control beliefs. The scores were obtained separately for the three sub scales. The study points towards the need for Intervention at the school level for empowering the females to focus their attention on their inner capabilities rather than external appearances.